ELECTRONIC LEARNER WORKSHEET BASED ON ARTICULATE STORYLINE 3 PLACE VALUE MATERIAL FOR GRADE II ELEMENTARY SCHOOL LEARNERS - Ni’mah, Khilyatu; Triwahyuningtyas , Dyah; Suastika , I Ketut (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Student Worksheets in Elementary Schools still rarely apply technology in learning. The Student Worksheets currently circulating in schools are still general in nature and there are no specific instructions for using Student Worksheets for teachers and students. The aim of this research is to develop mathematics teaching materials, especially place value material in Grade II Elementary Schools and measure the feasibility, effectiveness and practicality of the Electronic Student Worksheets developed. This research uses the ADDIE model. The instruments used for data collection are questionnaires and documentation. The questionnaire consists of a material expert, media expert, practitioner (teacher) questionnaire and a student response questionnaire. Data analysis techniques use quantitative and qualitative descriptive. The research results obtained from the feasibility test mean the average percentage of media experts and material experts is 83.35%. The practicality test obtained an average of 88.3% from teacher and student response questionnaires. The effectiveness test obtained an average of 0.79. Based on the data obtained, the Electronic Student Worksheet Based on Articulate Storyline 3 was declared feasible, practical and effective for use at the elementary school level. Researchers hope that this research can add new experiences in learning and can be used as a reference for other similar research.